ANALISIS KREATIVITAS SISWA DALAM PEMANFAATAN BARANG BEKAS DALAM PROJEK PENGUATAN PROFIL PELAJAR PANCASILA PADA SISWA KELAS V SDN 25 BETUNG - Mutiara. S (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the form of creativity shown by students in processing used goods into useful products, and to analyze student independence in the process of designing and making works. Using a descriptive qualitative approach. Data collection techniques were carried out through direct observation of P5 activities, interviews with the principal, grade V teachers and grade V students, and documentation of student work. The subjects of the study were 18 grade V students of SDN 25 Betung. The results of the study showed that most students showed a fairly high level of creativity in designing and making products from used goods such as making hanging mini pots and composting them using dry leaves (biohdrogen). Students developed new ideas, used various recycled materials, and conveyed ideas independently and collaboratively. Overall, this activity had a positive impact on shaping students' character such as, believing and being devoted to God Almighty, independence, creativity, and concern for the environment. Thus, the Pancasila Student Profile Strengthening Project activity based on the utilization of used goods has proven to be effective in fostering creativity while strengthening the values ​​of the Pancasila Student Profile.